2015
DOI: 10.1039/c4ra16247a
|View full text |Cite
|
Sign up to set email alerts
|

Continuous polyacrylonitrile nanofiber yarns: preparation and dry-drawing treatment for carbon nanofiber production

Abstract: Drawing of electrospun polyacrylonitrile nanofiber yarns in dry conditions can significantly improve tensile strength as well as fiber and yarn quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 41 publications
(46 reference statements)
1
42
0
Order By: Relevance
“…Electrospinning Nanofibers and Nanoyarns Nanofibers and nanoyarns were electrospun using a similar setup described in our previous work, 21 which was based off of a system designed by Xie et al 22 Briefly, as shown in Figures (1 and 2)(a, b), the electrospinning setup consisted of two high voltage power supplies (Gamma High Voltage Research, Ormond Beach, Florida), two syringe pumps (Harvard Apparatus, Plymouth Meeting, Pennsylvania), each equipped with a syringe and needle, and a copper funnel (Destilarias Eau.de.Vie, Portugal, diameter 120 mm). The high voltage power supplies were connected to the needle tips using alligator clips.…”
Section: Methodsmentioning
confidence: 99%
“…Electrospinning Nanofibers and Nanoyarns Nanofibers and nanoyarns were electrospun using a similar setup described in our previous work, 21 which was based off of a system designed by Xie et al 22 Briefly, as shown in Figures (1 and 2)(a, b), the electrospinning setup consisted of two high voltage power supplies (Gamma High Voltage Research, Ormond Beach, Florida), two syringe pumps (Harvard Apparatus, Plymouth Meeting, Pennsylvania), each equipped with a syringe and needle, and a copper funnel (Destilarias Eau.de.Vie, Portugal, diameter 120 mm). The high voltage power supplies were connected to the needle tips using alligator clips.…”
Section: Methodsmentioning
confidence: 99%
“…However, the intensity of the diffraction peak of filaments became stronger with the increase of drawing ratios, especially at the 2θ angle of 21.6 , which indicated increase in crystallinities of filaments (as shown in Figure 13b). When postdrawing ratios increased, which meant larger tensile force was applied to filaments, more polymeric molecular chains in nanofibers could be more easily arranged regularly [33,34], the distance between adjacent molecular chains decreased at the same time, so more hydrogen bonds between molecular chains could be formed in nanofibers, indicating the amount of γ crystal increased [35,36]. In addition, some γ crystal could transform into α crystal under tensile force [37,38].…”
Section: Post-drawing Process Of As-spun Nanofiber Filamentsmentioning
confidence: 99%
“…More recently, researchers have developed modified electrospinning setups that form continuous, twisted nanofiber yarns in one system. 6,12,13,2123 Ali et al . built a modified electrospinning setup in which nanofibers were spun onto a rotary funnel collector, twisted into yarns, and collected onto a yarn winding system.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have developed modified electrospinning setups that form continuous, twisted nanofiber yarns in one system. 6,12,13,[21][22][23] Ali et al built a modified electrospinning setup in which nanofibers were spun onto a rotary funnel collector, twisted into yarns, and collected onto a yarn winding system. 7 The researchers studied the dependences of nanofiber and yarn diameters on several electrospinning parameters, including flow rate and applied voltage.…”
Section: Introductionmentioning
confidence: 99%